Investments in Shares of Islamic Studies Thinking Jasser Auda - Mutawalli Mursyid Al-basyar; Indah Yuliana (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
At some Muslims there who think that the investment of Islamic stocks is not allowed (forbidden) because it does not conform to the Islamic shariah. But the majority of Muslims believe that sharia stock investing is one form of activity muamalah have to meet the principles of Shariah. The purpose of this study was to determine the investment practices of Islamic stocks on Islamic Capital Markets viewed from the perspective of Maqashid Sharia Jasser Auda view. This type of research is used in this research is qualitative normative research, with the kind of approach to the study of literature (literature research) with the source of data is secondary data obtained from previous studies, and other reference sources. Basically, buying and selling shares of Shariah in progress by continuing to pay more attention to the rights of the individual investors who make investments. Further investment of Islamic stocks if observed from the aspect of sharia perspective maqashid Jasser Auda is Maqashid Ammah, Maqashid Khassah, dan Maqashid Juz’iyyah can be said that at this stage in practice, sharia stock investment has fulfilled the three categories Maqasid the ash -Shariah.